Transtorno de déficit de atenção/hiperatividade em crianças e adolescentes com epilepsias de difícil controle : influência do tratamento com Metilfenidato sobre a qualidade de vida - Radziuk, Ana Lucia Germano da Silva (2010)
Rationale: Comorbidity between difficult-to-treat epilepsies and ADHD is high, but because of concerns with the use of stimulants in this population, there is no data on the possible impact of such treatment.Objective: We studied the effect of methylphenidate in the quality of life of children and adolescents with DSM-IV criteria for ADHD and difficult-to-treat epilepsies.Methods: Open label, non-controlled trial, with intention-to-treat analysis following 30 patients for 6 months. Subjects received methylphenidate following 3 months of baseline, during which antiepileptic drugs (AEDs) were adjusted and epilepsy, ADHD and quality of life variables were assessed. Multivariate regression analysis identified the main variables correlated with outcome.Results: Only one patient withdrew because of seizure worsening. Following methylphenidate introduction, reaching doses of 0.40 - 0.50 mg/kg/day, a marked improvement in quality of life scores and a significant reduction in seizure frequency and severity were observed. Female sex, reduction of core ADHD symptom burden and tolerability to adequate doses of methylphenidate correlated with quality of life scores.Conclusion: These preliminary data suggest that methylphenidate treatment is safe and effective to patients with ADHD and difficult-to-treat epilepsies and has a positive impact on quality of life scores